Survival Outcomes and Prognostic Factors of Borderline Ovarian Tumors - Phansenee Supreechaya; Charuwan Tantipalakorn; Tanarat Muangmool; Kittipat Charoenkwan; Prapaporn Suprasert; Jatupol Srisomboon (Asian Pacific Journal of Cancer Care, 2021)
Background and Objective: Borderline ovarian tumor (BOT) is a distinct but heterogeneous group of tumors defined by histopathology as atypical epithelial proliferation without stromal invasion. Women with BOT are usually younger than those with invasive carcinoma. This study aimed to evaluate the survival outcomes and prognostic factors of patients with BOT in a single institute in the northern region of Thailand. Methods: The medical records of patients with BOT who were treated at Chiang Mai University Hospital between January 1, 2008 and December 31, 2019 were reviewed. The survival outcomes were analyzed by the Kaplan-Meier method and prognostic factors were analyzed by univariate and multivariate approaches. Results: 168 patients with BOT were enrolled in the study. The median age was 48.8 years. At the median follow-up time of 25.4 months, 9 patients (5.3%) developed recurrence and 2 (1.1%) experienced progression to invasive carcinoma. The 5-year progression-free survival (PFS) and overall survival were 93.2% and 97.4%, respectively. By univariate analysis, advanced stage (p=0.02), tumor size smaller than 10 cm (p=0.03), conservative surgery (p=0.03), and bilateral tumors (p=0.07) were significantly associated with worse PFS. Hysterectomy was a protective factor for recurrence with the hazard ratio of 0.09 (95% CI, 0.01 – 0.77; p= 0.03). Cell types, pelvic lymphadenectomy, micro-invasion, and non-invasive peritoneal implant did not significantly affect PFS. By multivariate analysis, early stage (p=0.01), tumor size larger than 10 cm (p=0.04), and hysterectomy (p=0.03) were significantly associated with better survival. Conclusion: Patients with BOT had excellent survival outcomes. Tumor size of larger than 10 cm, early-stage disease, and hysterectomy were significant prognostic factors for better survival outcomes. Conservative surgery should be offered to patients who desire to preserve future fertility and long-term follow-up is needed to assure recurrence - free.